Usefulness of PET With [18F]LBT-999 for the Evaluation of Presynaptic Dopaminergic Neuronal Loss in a Clinical Environment - Ribeiro, Maria-Joao; Vercouillie, Johnny; Arlicot, Nicolas; Tauber, Clovis; Gissot, Valérie; Mondon, Karl; Barantin, Laurent; Cottier, Jean-Philippe; Maia, Serge; Deloye, Jean-Bernard; Emond, Patrick; Guilloteau, Denis (Frontiers in Neurology, 2020)
Purpose: The density of the neuronal dopamine transporter (DAT) is directly correlated with the presynaptic dopaminergic system injury. In a first study, we evaluated the brain distribution and kinetics of [18F]LBT-999, a DAT PET radioligand, in a group of eight healthy subjects. Taking into account the results obtained in healthy volunteers, we wanted to evaluate whether the loss of presynaptic striatal dopaminergic fibers could be estimated, under routine clinical conditions, using [18F]LBT-999 and a short PET acquisition. Materials and methods: Six patients with Parkinson's disease (PD) were compared with eight controls. Eighty-nine minutes of dynamic PET following an intravenous injection of [18F]LBT-999 were acquired. Using regions of interest for striatal nuclei, substantia nigra (SN), cerebellum, and occipital cortex, defined over each T1 3D MRI, time–activity curves (TACs) were obtained. From TACs, binding potential (BPND) using the simplified reference tissue model and distribution volume ratios (DVRs) using Logan graphical analysis were calculated. Ratios obtained for a 10-min image, acquired between 30 and 40 min post-injection, were also calculated. Cerebellum activity was used as non-specific reference region. Results: In PD patients and as expected, striatal uptake was lower than in controls which is confirmed by BPND, DVR, and ratios calculated for both striatal nuclei and SN, significantly inferior in PD patients compared with controls (p < 0.001). Conclusions: PET with [18F]LBT-999 could be an alternative to assess dopaminergic presynaptic injury in a clinical environment using a single 10 min acquisition.